PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Chinthia Surya Wijaya; Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study is to obtain empirical evidence on the effect of liquidity, profitability, leverage and activity ratios on financial distress in property and real estate companies listed in Indonesia Stock Exhange during 2017-2019. The sample was selected using purposive sampling method with a total sample of 135 companies. This study uses secondary data which was tested using logistic regression analysis and helped by Eviews 11. The results of this study showed that profitability ratio has a negative effect on financial distress while the liquidity ratio, leverage and activity have no effect on financial distress. The implication of this research is the importance of increasing the profitability ratio to provide good signal to investors that the company finances are in a healthy condition.